Study on Mechanical Properties and Failure Mechanism of Axial Braided C/C Composite - Chunguang Wang; Weiping Tian; Min Tang (International Journal of Aerospace Engineering)
In order to study the mechanical properties and failure mechanism of the axial braided C/C composites, the microscopic and macroscopic mechanical properties of the composite were investigated. In view of the size effect of the samples, the properties of the samples with different thickness were tested. The strain during loading was measured by optical method, and the failure morphology was observed by SEM. The changing characteristics of stress-strain curve were analyzed, and the failure characteristics of materials and failure mechanism under various loads were obtained. It was found that brittle fracture was observed during the tensile process of axial braided C/C composites, and the main failure forms were fiber rod pulling and partial fiber rod breaking in the axial direction. Radial failure was mainly in the form of fiber bundle fracture and crack stratification propagation. When compressed, the material exhibited pseudoplastic characteristics. The radial compression sample was cut along a 45-degree bevel. The axial compression curve was in the form of double fold, the axial fiber rod was unstable, and the transverse fiber bundle was cut. During in-plane shearing, the axial fracture was brittle and the fiber rod was cut. The radial direction showed the fracture and pulling of the fiber bundle, and the material had the characteristics of pseudoplasticity. The research methods and results in this paper could provide important references for the optimization and rational application of C/C composite materials.